Glioblastoma-synthesized G-CSF and GM-CSF contribute to growth and immunosuppression: Potential therapeutic benefit from dapsone, fenofibrate, and ribavirin. Issue 5 (April 2017) - Kast, Richard E; Hill, Quentin A; Wion, Didier; Mellstedt, Håkan; Focosi, Daniele; Karpel-Massler, Georg; Heiland, Tim; Halatsch, Marc-Eric
Increased ratio of circulating neutrophils to lymphocytes is a common finding in glioblastoma and other cancers. Data reviewed establish that any damage to brain tissue tends to cause an increase in G-CSF and/or GM-CSF (G(M)-CSF) synthesized by the brain. Glioblastoma cells themselves also synthesize G(M)-CSF. G(M)-CSF synthesized by brain due to damage by a growing tumor and by the tumor itself stimulates bone marrow to shift hematopoiesis toward granulocytic lineages away from lymphocytic lineages. This shift is immunosuppressive and generates the relative lymphopenia characteristic of glioblastoma. Any trauma to brain—be it blunt, sharp, ischemic, infectious, cytotoxic, tumor encroachment, or radiation—increases brain synthesis of G(M)-CSF. G(M)-CSF are growth and motility enhancing factors for glioblastomas. High levels of G(M)-CSF contribute to the characteristic neutrophilia and lymphopenia of glioblastoma. Hematopoietic bone marrow becomes entrained with, directed by, and contributes to glioblastoma pathology. The antibiotic dapsone, the lipid-lowering agent fenofibrate, and the antiviral drug ribavirin are Food and Drug Administration– and European Medicines Agency–approved medicines that have potential to lower synthesis or effects of G(M)-CSF and thus deprive a glioblastoma of some of the growth promoting contributions of bone marrow and G(M)-CSF.